Model-based Analysis and Specification of Functional Requirements and Tests for Complex Automotive Systems - Wiecher, Carsten; Mandel, Constantin; Günther, Matthias; Fischbach, Jannik; Greenyer, Joel; Greinert, Matthias; Wolff, Carsten; Dumitrescu, Roman; Mendez, Daniel; Albers, Albert (arXiv preprint)

Evaluation of Industry 4.0 Applications in Production - Joppen, Robert; Kühn, Arno; Förster, Magdalena; Dumitrescu, Roman (Journal of the Knowledge Economy)
Abstract Industry 4.0 promises many potentials in production. Examples are a data-driven optimization of production processes of individual machines, driverless transport systems, and assistance systems. Nevertheless, companies are still hesitant to invest in Industry 4.0 applications. Studies show that one of the main reasons for that is the unclear economic benefit. In this work, we present a systematic approach for the evaluation of Industry 4.0 applications in production. The main goal of the systematic is to create transparency over the evaluation process of an investment in an Industry 4.0 application in production. The evaluation of a concrete technical solution in an existing production system is supported. As a theoretical foundation, a characterization of investments in Industry 4.0 applications is given. From that, a procedure model is derived. It puts the activities to be carried out, the tools to be used and results in a temporal context. The application of the systematic is shown on the basis of an application example.
Keywords: Economics and Econometrics

Collaborative Modeling of Use Case & Damage Scenarios in Online Workshops Using a 3D Environment - Japs, Sergej; Schmidt, Sebastian; Kargl, Frank; Kaiser, Lydia; Kharatyan, Aschot; Dumitrescu, Roman (Proceedings of the Design Society)
Abstract The development of technical systems requires close cooperation of stakeholders from different disciplines. This collaboration takes place in workshops. Driven by digitalization and by the current pandemic such workshops take place primarily online. Suitable collaboration tools and methods are crucial to success. At the beginning of such workshops, use and damage scenarios are identified. In this paper, we presented a method and tool for identifying and modeling use and damage scenarios, which we evaluated in 14 online workshops with a total of 118 participants over a period of almost 3 years.

Why make it hard? - Usage of aggregated statistical data for risk assessment of damage scenarios in the context of ISO/SAE 21434 - Japs, Sergej; Kargl, Frank; Anacker, Harald; Dumitrescu, Roman (Procedia CIRP)
Keywords: General Medicine

Efficient method for determining substrate parameters of additive manufactured spatial circuit carriers - Mager, Thomas; Jürgenhake, Christoph; Dumitrescu, Roman (2022 14th German Microwave Conference (GeMiC))

Use Case Driven Digital Twin Generation - Gollner, Denis; Klausmann, Tobias; Rasor, Rik; Dumitrescu, Roman (2022 IEEE 5th International Conference on Industrial Cyber-Physical Systems (ICPS))

Requirements analysis for an intelligent workforce planning system: a socio-technical approach to design AI-based systems - Gabriel, Stefan; Bentler, Dominik; Grote, Eva-Maria; Junker, Caroline; Wendischhoff, David Meyer zu; Bansmann, Michael; Latos, Benedikt; Hobscheidt, Daniela; Kühn, Arno; Dumitrescu, Roman (Procedia CIRP)
Keywords: General Medicine

Cross-industry methods for strategic planning of the digital transformation of small and medium sized enterprises - Förster, Magdalena; Kürpick, Christian; Hobscheidt, Daniela; Kühn, Arno; Dumitrescu, Roman (Procedia CIRP)
Keywords: General Medicine

Security- and Safety-Driven Functional Architecture Development Exemplified by Automotive Systems Engineering - Kharatyan, Aschot; Günther, Matthias; Anacker, Harald; Japs, Sergej; Dumitrescu, Roman (Procedia CIRP)
Keywords: General Medicine

Method for direct end customer integration into the agile product development - Humpert, Lynn; Röhm, Benjamin; Anacker, Harald; Dumitrescu, Roman; Anderl, Reiner (Procedia CIRP)
Keywords: General Medicine

Development of a Numerical 3D Model for Analyzing Clinched Joints in Versatile Process Chains - Bielak, C. R.; Böhnke, M.; Bobbert, M.; Meschut, G. (The Minerals, Metals & Materials Series)

Verhandlungen sexueller und kultureller Fremd- und Selbstbestimmungen in Kristina Aamand’s interkulturellem Adoleszenzroman „Wenn Worte meine Waffe wären“ - Zierau, Cornelia; Kofer, Martina (Interkulturelles Lernen mit Kinder- und Jugendliteratur (in Vorbereitung))

Wertorientierung und Werteverhandlungen in Emine Sevgi Özdamars Roman „Das Leben ist eine Karawanserei“ - Zierau, Cornelia (Türkisch-deutsche Studien Jahrbuch 2020: Wertorientierungen)

Türkisch-deutsche Studien Jahrbuch 2020: Wertorientierungen

Increasing Firm Performance through Industry 4.0—A Method to Define and Reach Meaningful Goals - Koldewey, Christian; Hobscheidt, Daniela; Pierenkemper, Christoph; Kühn, Arno; Dumitrescu, Roman (Sci)

Collaborative Modeling of Interoperable Digital Twins in a SoS Context - Göllner, Denis; Rasor, Rik; Anacker, Harald; Dumitrescu, Roman (Procedia CIRP)
Keywords: General Medicine

Potentials and challenges of analyzing use phase data in product planning of manufacturing companies - Meyer, Maurice; Fichtler, Timm; Koldewey, Christian; Dumitrescu, Roman (Artificial Intelligence for Engineering Design, Analysis and Manufacturing)
The successful planning of future product generations requires reliable insights into the actual products’ problems and potentials for improvement. A valuable source for these insights is the product use phase. In practice, product planners are often forced to work with assumptions and speculations as insights from the use phase are insufficiently identified and documented. A new opportunity to address this problem arises from the ongoing digitalization that enables products to generate and collect data during their utilization. Analyzing these data could enable their manufacturers to generate and exploit insights concerning product performance and user behavior, revealing problems and potentials for improvement. However, research on analyzing use phase data in product planning of manufacturing companies is scarce. Therefore, we conducted an exploratory interview study with decision-makers of eight manufacturing companies. The result of this paper is a detailed description of the potentials and challenges that the interviewees associated with analyzing use phase data in product planning. The potentials explain the intended purpose and generic application examples. The challenges concern the products, the data, the customers, the implementation, and the employees. By gathering the potentials and challenges through expert interviews, our study structures the topic from the perspective of the potential users and shows the needs for future research.
Keywords: Artificial Intelligence; Industrial and Manufacturing Engineering

EngOps – Ein Leitbild für das agile Zusammenwirken von Engineering und Operations - Anacker, Harald; Dumitrescu, Roman; Michels, Nico; Rasor, Rik (Zeitschrift für wirtschaftlichen Fabrikbetrieb)
Abstract Um global erfolgreich zu bleiben, wird es bald nicht mehr ausreichen, Kriterien wie ein gutes Produktdesign zu erfüllen. Stattdessen muss der Kundennutzen kontinuierlich über den Produktlebenszyklus hinaus gesteigert werden. Tech-Konzerne verzeichnen bereits Erfolge und verkörpern den Wandel schon heute. Vor diesem Hintergrund ist ein neues Leitbild in der Entwicklung und dem Betrieb von zukünftigen, technischen Systemen erforderlich. EngOps soll diesen Bedarf decken und steht für die agile Kollaboration zwischen Engineering und Operations. Alle Teile des Unternehmens sollen ständig miteinander kooperieren, um so beispielsweise wandelbare Produkte auch nach dem Verkauf entwickeln zu können.
Keywords: Management Science and Operations Research; Strategy and Management; General Engineering

Giant Orbital Anisotropy with Strong Spin–Orbit Coupling Established at the Pseudomorphic Interface of the Co/Pd Superlattice - Kim, Sanghoon; Pathak, Sachin; Rhim, Sonny H.; Cha, Jongin; Jekal, Soyoung; Hong, Soon Cheol; Lee, Hyun Hwi; Park, Sung‐Hun; Lee, Han‐Koo; Park, Jae‐Hoon; Lee, Soogil; Steinrück, Hans-Georg; et al. (Advanced Science)
Keywords: General Physics and Astronomy; General Engineering; Biochemistry; Genetics and Molecular Biology (miscellaneous); General Materials Science; General Chemical Engineering; Medicine (miscellaneous)

An In-depth Study of Java Deserialization Remote-Code Execution Exploits and Vulnerabilities - Sayar, Imen; Bartel, Alexandre; Bodden, Eric; Le Traon, Yves (ACM Transactions on Software Engineering and Methodology)
Nowadays, an increasing number of applications uses deserialization. This technique, based on rebuilding the instance of objects from serialized byte streams, can be dangerous since it can open the application to attacks such as remote code execution (RCE) if the data to deserialize is originating from an untrusted source. Deserialization vulnerabilities are so critical that they are in OWASP’s list of top 10 security risks for web applications. This is mainly caused by faults in the development process of applications and by flaws in their dependencies, i.e., flaws in the libraries used by these applications. No previous work has studied deserialization attacks in-depth: How are they performed? How are weaknesses introduced and patched? And for how long are vulnerabilities present in the codebase? To yield a deeper understanding of this important kind of vulnerability, we perform two main analyses: one on attack gadgets, i.e., exploitable pieces of code, present in Java libraries, and one on vulnerabilities present in Java applications. For the first analysis, we conduct an exploratory large-scale study by running 256 515 experiments in which we vary the versions of libraries for each of the 19 publicly available exploits. Such attacks rely on a combination of gadgets present in one or multiple Java libraries. A gadget is a method which is using objects or fields that can be attacker-controlled. Our goal is to precisely identify library versions containing gadgets and to understand how gadgets have been introduced and how they have been patched. We observe that the modification of one innocent-looking detail in a class – such as making it public – can already introduce a gadget. Furthermore, we noticed that among the studied libraries, 37.5% are not patched, leaving gadgets available for future attacks. For the second analysis, we manually analyze 104 deserialization vulnerabilities CVEs to understand how vulnerabilities are introduced and patched in real-life Java applications. Results indicate that the vulnerabilities are not always completely patched or that a workaround solution is proposed. With a workaround solution, applications are still vulnerable since the code itself is unchanged.
Keywords: Software